HUMAN BITEMARKS: The fingerprints of the mouth - K Shashikala (Wolters Kluwer Medknow Publications, 2003)
The human dentition can be used as a weapon of attack or defense. It has been noticed by investigators that at some crime scenes, criminals seem to leave their bite impressions on food products, chewing gum, or more commonly on the skin of their victims, especially in cases of battery, rape, child abuse, and homicide. Many bite injuries are seen in casualty departments where quick and proper recovery of evidence can assist in analyzing these injuries. This article describes different bite marks, methods of preserving and collection of evidence, comparative analysis methods and a few interesting case reports